Poverty and food insecurity during COVID-19: Phone-survey evidence from rural and urban Myanmar in 2020 - Headey, Derek D.; Goudet, Sophie; Lambrecht, Isabel B.; Maffioli, Elisa Mari; Oo, Than Zaw; Russell, Toth (Elsevier, 2022)
Myanmar first experienced the COVID-19 crisis as a relatively brief economic shock in early 2020, before the economy was later engulfed by a prolonged surge in COVID-19 cases from September 2020 onwards. To analyze poverty and food security in Myanmar during 2020 we surveyed over 2000 households per month from June–December in urban Yangon and the rural dry zone. By June, households had suffered dramatic increases in poverty, but even steeper increases accompanied the rise in COVID-19 cases from September onwards. Increases in poverty were much larger in urban areas, although poverty was always more prevalent in the rural sample. However, urban households were twice as likely to report food insecurity experiences, suggesting rural populations felt less food insecure throughout the crisis.